Primary pulmonary hepatoid adenocarcinoma: A case report. (2015) - Al-Najjar, Haider; Evison, Matthew; Doran, Helen; Booton, Richard; Taylor, Paul
Abstract: We herein report a case of primary pulmonary hepatoid adenocarcinoma in a 71 year old man and provide an overview on knowledge and existing reports of this rare tumour. Primary pulmonary hepatoid adenocarcinoma is an AFP-producing lung tumour composed of neoplastic cells morphologically resembling hepatocellular carcinoma. The main challenge for physicians encountering such tumours is distinguishing between hepatocellular carcinomas and pulmonary hepatoid adenocarcinomas. Previous literature is conflicting, particularly around the distinguishing immunohistochemical characteristics of the two tumours. Given the rarity of this tumour and paucity of published literature, we believe the clinical–radiological characteristics provide the key to diagnosis and aim to demonstrate this in our case. Highlights: Primary pulmonary hepatoid adenocarcinoma is an AFP-producing lung tumour. It is rare with only 14 previous reported cases. It is composed of cells morphologically resembling hepatocellular carcinoma. The challenge to clinicians is to distinguish these two conditions. In our case report the clinical–radiological picture helped establish the diagnosis.